On the Best Polynomial Approximations of $2π$-Periodic Functions and Exact Values of $n$-Widths of Functional Classes in the Space $L_2$ - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
To solve extremal problems of approximation theory in the space $L_2$, we use τ-moduli introduced by Ivanov. We determine the exact values of constants in Jackson-type inequalities and the exact values of $n$-widths of functional classes determined by these moduli.